(Invited) SiGe BiCMOS for Optoelectronics. (18th August 2016) - Knoll, Dieter; Lischke, Stefan; Awny, Ahmed; Zimmermann, Lars
Abstract : Silicon-based electronic-photonic integrated circuit (ePIC) technology enables a high degree of integration of optoelectronic subsystems for optical communications. In this paper we give an overview about IHP's work in ePIC technology development under use of different SiGe BiCMOS baseline processes. Focus is on "Photonic BiCMOS", a new monolithic ePIC technology which combines high-performance BiCMOS technology with high-speed photonic devices for electronic-photonic submodules for next generation communication networks. Main features of this technology are described, including an overview of offered photonic and electronic devices. Examples of demonstrator circuits fabricated in the new technology are also presented. Another approach of merging photonics with electronics is hybrid assembly. In a second part of the paper we will demonstrate the potential of SiGe BiCMOS as the 'electronics supplier' for this approach.